Diel peroxy radicals in a semi industrial coastal area: nighttime formation of free radicals - Sinha, V. (Atmospheric Chemistry and Physics, 2012)
Peroxy radicals were measured by a PeRCA (Peroxy Radical Chemical Amplifier) instrument in the boundary layer during the DOMINO (Diel Oxidant Mechanisms In relation to Nitrogen Oxides) campaign at a coastal, forested site influenced by urban-industrial emissions in Southern Spain in late autumn. Total peroxy radicals (RO2* =HO2 +ΣRO2) generally showed a daylight maximum between 10 and 50 pptv at 13:00UTC, with an average of 18 pptv over the 15 days of measurements. Emissions from the industrial area of Huelva often impacted the measurement site at night during the campaign. The processing of significant levels of anthropogenic organics leads to an intense nocturnal radical chemistry accompanied by formation of organic peroxy radicals at comparable levels to those of summer photochemical conditions with peak events up to 60–80 pptv. The RO2 production initiated by reactions of NO3 with organic trace gases was estimated to be significant but not sufficient to account for the concentrations of RO2* observed in air masses carrying 15 high pollutant loading. The nocturnal production of peroxy radicals seems therefore to be dominated by ozonolysis of volatile organic compounds. RO2* diurnal variations were consistent with other HO2 measurements available at the site. HO2/RO2* ratios generally varied between 0.3 and 0.4 in all wind directions. Occasional HO2/RO2* ≥1 seemed to be associated with periods of high RO2* variability and with RO2 interferences in the HO2 measurement in air masses with high RO2 load.
Only IISERM authors are available in the record.